PENGARUH KEPERCAYAAN NASABAH, BIAYA ADMINISTRASI, DAN MANFAAT TERHADAP KEPUTUSAN NASABAH MENGGUNAKAN PRODUK TABUNGAN WADIAH PADA BANK SYARIAH INDONESIA (Studi Kasus Yayasan Irsyadul Ibad Pandeglang) - Nurliana, Lia (ITB AAS INDONESIA Surakarta, 2025)
Abstract This study aims to analyze the influence of customer trust, administrative fees, and perceived benefits on customers’ decisions to use Wadiah savings products at Bank Syariah Indonesia. A quantitative approach was employed through a survey conducted among teachers at the Irsyadul Ibad Foundation in Pandeglang. The results reveal that customer trust has a significant influence on the decision to use Wadiah savings, followed by perceived benefits. Meanwhile, administrative fees were found to have no significant effect. These findings highlight that improving customer trust and perceived benefits are the main drivers in encouraging customers to choose Islamic banking products. This research provides important implications for the development of marketing strategies and service improvements in the Islamic banking sector. Keywords: Bank Syariah Indonesia, Administrative Fees, Customer Trust, Customer Decision, Benefits, Wadiah Savings